Pseudonim - Benčić, Živa (Array, 2002)
Trying to determine the types of pseudonyms, the author starts from the role pseudonyms play in relation to the identity of the bearer, and based upon that, distinguishes and analyzes five types of pseudonymity: 1. pseudonyms whose main task is to hide the true identity of the bearer ; 2. pseudonyms which, while hiding the writer's true identity, help the meticulous construction of his/her false identity - which is the case with mystification ; 3. pseudonyms used in order to highlight some important aspects of the author's personal or artistic identity, and which should therefore be understood not as the author's false name, but his/her "true one", in Plato's sense of word (Kratil) ; 4. pseudonyms which the authors use for pragmatic reasons (because of homonymy or unattractiveness of their real name) ; 5. ludic pseudonyms, which are not the result of social or psychological pressure put on the writer, but are formed according to the immanent rules of the aesthetic game.